Medial Femoral Condyle Cartilage Defect Biomechanics: Effect of Obesity, Defect Size, and Cartilage Thickness. (February 2016) - Lacy, Kyle W.; Cracchiolo, Allison; Yu, Stephen; Goitz, Henry
Background: Medial femoral condyle (MFC) chondral defects cause knee pain. Clinical studies have shown worse functional outcomes and cartilage defect fill rates after microfracture in obese patients (BMI ≥30) and for defects with size ≥2 cm 2 . Purpose: To determine the effect of obesity, defect size, and cartilage thickness on the force sustained at the base of full-thickness MFC cartilage defects during weightbearing. Study Design: Controlled laboratory study. Methods: Eight human cadaveric knees were loaded in 15° of flexion. A sensor measured force across the medial compartment. The area at the base of the defect protected from load, termed the "area of containment, " was quantified, and loads simulating weightbearing for BMIs of 20, 30, and 40 were applied. A full-thickness cartilage defect was created on the MFC. Cycles of loads were applied for defect sizes with diameters of 6, 8, 10, 12, 14, 16, 18, and 20 mm. A second sensor recorded force at the base of the defect for defects with diameters of 14, 16, 18, and 20 mm. Results: Loads simulating BMI ≥30 led to a decrease in the area of containment for all defects ≥14 mm in diameter ( P ≤ .038). Base of defect force increased for defects ≥16 mm in diameter (area, ≥2 cm 2 ) between loaded and unloaded states ( P ≤ .042) and for loads simulating BMI ≥30 ( P ≤ .045). Cartilage rim thickness <2 mm showed higher base of defect force than did thickness ≥2 mm, for all BMI groups ( P ≤ .025). Conclusion: Increased force at the base of MFC cartilage defects was observed for weightbearing loads simulating BMI ≥30, for defect size ≥2 cm 2, and for rim thickness <2 mm. This may lead to a biomechanically unfavorable environment after microfracture in these patient subsets. Clinical Relevance: These biomechanical findings corroborate clinical studies that have noted worse outcomes after microfracture in patients with BMI ≥30 and cartilage defects of size ≥2 cm 2 . Further clinical studies are needed to compare microfracture with other cartilage restoration procedures in these patient subsets.